Physicochemical modeling of myricetin complexes by Zinc II ions - CHABI, Doco Rodrigue; KPOTA HOUNGUE, MAHUGBE TATA ALICE; KUEVI, Urbain; ATOHOUN, Guy Sylvain (My University, 2023)
Myricetin is phenolic compound, commonly found in vegetable kingdom (fruits, vegetables, roots etc.) and an integral part of daily diet of humans. Several experimental and theoretical works have shown that this molecule has an important antioxidant power. Indeed, since the discovery of relationship between antioxidant activity of certain phenolic compounds and their ability to chelate metal ions, many experimental studies devoted to complexation of molecules such as quercetin, myricetin, kaempferol, rutin, morine with various metals (Cobalt, Nickel, Zinc, Copper, Molybdenum, Europium) were realized. However, these experimental studies do not yet constitute a standard means of determining complexation sites of molecules. In present work, study of complexation of myricetin by Zn2+ ion was carried out by Hatree-Fock method, and in 6-311G (d, p) base set. The results of various calculations made it possible to:  release hydroxyl groups as myricetin complexation sites;  note that the complexes obtained are more antioxidants than myricetin;  show that the complexation of myricetin causes bathochromic shifts of absorption bands.
Keywords: Hatree-fock; myricetin; complexe; antioxidant